2007
DOI: 10.1037/0021-843x.116.3.498
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress disorder symptoms, physiological reactivity, alcohol problems, and aggression among military veterans.

Abstract: This study examined the association between posttraumatic stress disorder (PTSD) symptomatology and aggressive behavior among a sample of male Vietnam veterans (N = 1,328). Results indicated that the hyperarousal PTSD symptom cluster evidenced the strongest positive association with aggression at the bivariate level when compared with the other PTSD symptom clusters. When the PTSD symptom clusters were examined together as predictors, hyperarousal symptoms evidenced a significant positive relationship with agg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
177
3
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(195 citation statements)
references
References 85 publications
14
177
3
1
Order By: Relevance
“…Moreover, our results suggest the relation between alcohol misuse and PTSD hyperarousal symptoms is more specifically associated with alcohol-related problems rather than the quantityfrequency of alcohol use. It may be that PTSD hyperarousal symptoms influence externalizing behaviours (for example, angry outbursts or impulsive behaviour), which in turn may develop into alcohol-related problems (for example, spousal abuse or driving while intoxicated 56 ). Alternatively, consumption of alcohol may reduce inhibitions that had previously held back externalizing behaviours prompted by hyperarousal symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our results suggest the relation between alcohol misuse and PTSD hyperarousal symptoms is more specifically associated with alcohol-related problems rather than the quantityfrequency of alcohol use. It may be that PTSD hyperarousal symptoms influence externalizing behaviours (for example, angry outbursts or impulsive behaviour), which in turn may develop into alcohol-related problems (for example, spousal abuse or driving while intoxicated 56 ). Alternatively, consumption of alcohol may reduce inhibitions that had previously held back externalizing behaviours prompted by hyperarousal symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…War veterans are 2-3% more likely to develop significant physical and mental health complications than civilian populations [1]. From physical rehabilitation due to bodily injury to cognitive rehabilitation due to traumatic brain injury (TBI), the physical and mental rehabilitation after combat injuries can be exhausting.…”
Section: Physical and Mental Health Risksmentioning
confidence: 99%
“…Many develop debilitating mental health complications. This paper addresses one of the most prevalent of these, post-traumatic stress disorder (PTSD) [1][2][3].…”
mentioning
confidence: 99%
“…Several studies have found general impairments of child rearing capacities, such as inadequate emotional reaction [8], impaired parent-child relationship [9,10], disrupted communication styles [11] or physical punishment [12][13][14][15]. Physical punishment was often explained by hyperarousal symptoms or substance abuse in the parents [16] and was associated with combat experiences in veteran fathers and behavioural problems in the offspring [17]. Similar to the dose effect for vulnerability to PTSD [18,19], a dose effect for the consequences of family violence was found: children who experienced more maltreatment in childhood demonstrated more severe behavioural problems and higher rates of delinquency [20,21].…”
Section: Introductionmentioning
confidence: 99%